Governance of advanced materials: Shaping a safe and sustainable future - Monique Groenewold; Eric A.J. Bleeker; Cornelle W. Noorlander; Adriënne J.A.M. Sips; Margriet van der Zee; Robert J. Aitken; James H. Baker; Martine I. Bakker; Evert A. Bouman; Shareen H. Doak; Damjana Drobne; Verónica I. Dumit; et al. (NanoImpact, 2024)

Correction to: Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)

Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)
Climate change scenarios predict more frequent and intense drought periods for 2071 to 2100 for many regions of the world including Austria. Current and predicted lower precipitation scenarios were simulated at a lysimeter station containing a fertile and less fertile agricultural soil for 9 years. 13 C and 15 N-labeled green manure was added in year 8 with the aim to analyze how the predicted precipitation regime affects soil fauna and microbial groups and consequently nitrogen (N) and carbon (C) cycling. Among the investigated mesofauna (collembola and oribatida), the abundance and biodiversity of oribatida was significantly reduced by drought, possibly because they mainly represent K-strategist species with low mobility and consequently the need to adapt to long-term adverse environmental conditions. Microbial community composition and microbial biomass, investigated by phospholipid fatty acid (PLFA) analysis, was indistinguishable between the current and the predicted precipitation scenarios. Nonetheless, soil 13 C-CO 2 emissions and soil water 15 N-NO 3 data revealed decelerated mineralization of green manure under reduced precipitation in the first 2 weeks, but no effects were observed on soil C sequestration or on 13 C incorporation into microbial PLFAs in the following 1.2 years. We found that over a 1-year time period, decomposition was rather driven by plant residue availability than water limitation of microorganisms in the investigated agroecosystem. In contrast, N 2 O emissions were significantly reduced under drought, and green manure derived 15 N accumulated in the soil under drought, which might necessitate the adjustment of future fertilization regimes. The impacts of reduced precipitation and drought were less pronounced in the more fertile agricultural soil, due to its greater buffering capacity in terms of water storage and organic matter and nutrient availability.

Deterministic influences exceed dispersal effects on hydrologically‐connected microbiomes - Emily B. Graham; Alex R. Crump; Charles T. Resch; Sarah Fansler; Evan Arntzen; David W. Kennedy; Jim K. Fredrickson; James C. Stegen (Environmental Microbiology, 2017)
Summary Subsurface groundwater‐surface water mixing zones (hyporheic zones) have enhanced biogeochemical activity, but assembly processes governing subsurface microbiomes remain a critical uncertainty in understanding hyporheic biogeochemistry. To address this obstacle, we investigated (a) biogeographical patterns in attached and waterborne microbiomes across three hydrologically‐connected, physicochemically‐distinct zones (inland hyporheic, nearshore hyporheic and river); (b) assembly processes that generated these patterns; (c) groups of organisms that corresponded to deterministic changes in the environment; and (d) correlations between these groups and hyporheic metabolism. All microbiomes remained dissimilar through time, but consistent presence of similar taxa suggested dispersal and/or common selective pressures among zones. Further, we demonstrated a pronounced impact of deterministic assembly in all microbiomes as well as seasonal shifts from heterotrophic to autotrophic microorganisms associated with increases in groundwater discharge. The abundance of one statistical cluster of organisms increased with active biomass and respiration, revealing organisms that may strongly influence hyporheic biogeochemistry. Based on our results, we propose a conceptualization of hyporheic zone metabolism in which increased organic carbon concentrations during surface water intrusion support heterotrophy, which succumbs to autotrophy under groundwater discharge. These results provide new opportunities to enhance microbially‐explicit ecosystem models describing hyporheic zone biogeochemistry and its influence over riverine ecosystem function.

Respiratory syncytial virus-associated hospitalizations over three consecutive seasons in children with congenital heart disease - B. Resch; S. Kurath-Koller; J. Hahn; W. Raith; M. Köstenberger; A. Gamillscheg (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Two nosocomial norovirus outbreaks in the neonatal intensive and intermediate care unit - C. Sommer; W. Mueller; B. Resch (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

CT-Operated Bifunctional Fluorescent Probe Based on a Pretwisted Donor–Donor–Biphenyl - Y. Q. Li; J. L. Bricks; U. Resch-Genger; M. Spieles; W. Rettig (Journal of Fluorescence, 2006)

Observational study of respiratory syncytial virus-associated hospitalizations and use of palivizumab in premature infants aged 29–32 weeks - B. Resch; W. Gusenleitner; W. D. Müller; J. Haas (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

How to Improve Quality Assurance in Fluorometry: Fluorescence-Inherent Sources of Error and Suited Fluorescence Standards - U. Resch-Genger; K. Hoffmann; W. Nietfeld; A. Engel; J. Neukammer; R. Nitschke; B. Ebert; R. Macdonald (Journal of Fluorescence, 2005)

Traceability in Fluorometry: Part II. Spectral Fluorescence Standards - U. Resch-Genger; D. Pfeifer; C. Monte; W. Pilz; A. Hoffmann; M. Spieles; K. Rurack; J. Hollandt; D. Taubert; B. Schönenberger; P. Nording (Journal of Fluorescence, 2005)

Traceability in Fluorometry—Part I: Physical Standards - J. Hollandt; R. D. Taubert; J. Seidel; U. Resch-Genger; A. Gugg-Helminger; D. Pfeifer; C. Monte; W. Pilz (Journal of Fluorescence, 2005)

Typical Frankia infect actinorhizal plants exotic to New Zealand - Michael L. Clawson; David R. Benson; Steven C. Resch; David W. Stephens; Warwick B. Silvester (New Zealand Journal of Botany, 1997)
Frankia strains are actinomycetes that fix N 2 in root nodules of plants classified in eight families of the Angiospermae. The wide variety of plants infected has raised questions about the ecology and diversity of Frankia symbionts, and their co‐evolution with actinorhizal plants. Partial sequencing was done of the small subunit (16S) rRNA gene from Frankia endophytes present in the root nodules of Alnus cordata , A. glutinosa , A. viridis , Casuarina equisetifolia, Coriaria arborea, C. plumosa , and Elaeagnus pungens growing in New Zealand. With the exceptions of the Coriaria spp., all of the plants are exotic to New Zealand. Analysis of the 16S rRNA gene indicates that the exotic species were nodulated by Frankia strains that cluster with strain groups previously shown to be typical for each actinorhizal host. Frankia in 12 native Coriaria spp. nodules yielded two sequences differing in only one position, suggesting a relatively low diversity compared with the exotic species.

Rasche Carboxihmoglobinbestimmung mittels nichtdispersiver Ultrarot-Gasanalyse - H. Hauck; M. Neuberger; W. Resch (Archives of Toxicology, 1976)